Gambaran Peran Pendamping Keluarga bagi Calon Pengantin untuk Mencegah Stunting di Desa Delik Kabupaten Semarang: Description of the Role of Family Companions for Prospective Brides to Prevent Stunting in the Delik Village, Semarang Regency - Yulianti; Vistra Veftisia (Journal of Holistics and Health Sciences (JHHS), 2023)
Family Companion is assistance to families who are prone to stunting. Interpreted as a series of activities which include counseling, facilitation of referral services and facilitation of social assistance with the aim of increasing access to information and services for families/families at risk of stunting such as pregnant women, postpartum mothers, children aged 0–59 months, and all prospective brides/PUS through 3-month pre-marital assistance as part of marriage services for early detection of stunting risk factors and making efforts to minimize/prevent the effects of stunting risk factors. The aim of the study was to describe the role of a family companion in the village of Delik, Tuntang sub-district, Semarang regency. This type of quantitative descriptive research uses a cross-sectional approach. The total population is 37 family companions. The sampling technique used the total sampling method with a questionnaire research instrument. Data analysis using frequency distribution. And for the results of identifying risk factors for giving birth to positive role stunting 23 respondents (62.2%), educating positive role 19 (51.4%), facilitating prospective brides to carry out efforts (treatment) to prevent positive role stunting birth 25 (67.6%), informing/ensuring the prospective bride and groom attending classes/obtaining positive role marriage guidance material 23 (62.2%), conducting positive role IEC 24 (64.9%), recording/reporting positive role 21 (56.8%) , The role of family companion in general is positive role 21 (56.8%). the role of a family companion for the bride and groom to prevent stunting in the village of Delik is a positive role for 21 respondents (56.8%).   ABSTRAK Pendamping Keluarga adalah pendampingan terhadap keluarga yang memiliki kerawanan stunting. Dimaknai sebagai  serangkaian kegiatan yang meliputi penyuluhan, fasilitasi pelayanan rujukan dan fasilitasi pemberian bantuan sosial yang bertujuan meningkatkan akses informasi dan pelayanan kepada keluarga/keluarga beresiko stunting seperti ibu hamil, ibu pasca persalinan, anak usia 0–59 bulan, serta semua calon pengantin/PUS melalui pendampingan 3 bulan pranikah sebagai bagian dari pelayanan nikah untuk deteksi dini faktor risiko stunting dan melakukan upaya meminimalisir /pencegahan pengaruh dari faktor risiko stunting. Tujuan penelitian untuk mengetahui gambaran peran pendamping keluarga di Desa Delik Kecamatan Tuntang Kabupaten Semarang Jenis penelitian Deskriftif Kuantitatif dengan pendekatan Cross Sectional. Jumlah populasi sebanyak 37 pendamping keluarga. Teknik pengambilan sampel menggunakan metode total sampling dengan instrument penelitian kuesioner. Analisa data menggunakan distribusi frekuensi. Dan untuk hasil mengidentifikasi faktor resiko melahirkan stunting peran positif 23 responden (62.2%) , mengedukasi peran positif 19 (51.4%), memfasilitasi calon pengantin melakukan upaya (treatment) pencegahan melahirkan stunting peran positif 25 (67.6 %), menginformasikan/memastikan calon pengantin mengikuti kelas/mendapatkan materi bimbingan perkawinan peran positif 23 (62.2 %), melakukan KIE peran positif 24  (64.9 %), melakukan pencatatan /pelaporan peran positif 21  (56.8%) ,  Peran pendamping keluarga secara umum peran positif 21 (56.8%). peran pendamping keluarga bagi calon pengantin untuk mencegah stunting di Desa Delik yaitu  peran positif sebanyak 21 responden (56.8%).